Digital Citizenship and Social Movements: How the Aksi Kamisan Discourse on Human Rights Enforcement Issues on Social Media - Dicky Zakaria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study discusses the practice of digital citizenship in an internet-based social movement. The phenomenon of social movement which is the locus of this research is the Aksi Kamisan. The Aksi Kamisan is a movement that was born as a result of the state not showing partiality to the process of upholding human rights in Indonesia. This research uses a qualitative approach with a descriptive type of research. The data source used is Instagram @aksikamisan upload. After the data is obtained, the researcher will manage it with content analysis to see how the Aksi Kamisan discusses the issue of human rights enforcement on Instagram. The results of the study show that Aksi Kamisan discusses the issue of human rights enforcement through uploading photos, videos and live broadcasts from the Aksi Kamisan Instagram account.